2018
DOI: 10.3390/sports6040117
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Post Activation Potentiation on Achilles Tendon Stiffness, Elasticity and Thickness among Basketball Players

Abstract: The purpose of this study is to examine and further understand the effects of post activation potentiation on Achilles tendon (AT) thickness, elasticity and stiffness among basketball players. Basketball is one of the world’s most popular and widely viewed sports. One of the main factors which athletes depend on during their performance is elastic energy coming straight from the AT. Contractile activity increases the muscular force and is known in science as post activation potentiation (PAP). Twelve basketbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…For instance, Klich et al [32] reported an acute increase in vastus lateralis stiffness after all-out 200 m and 4000 m track cycling, with a higher increase after 200 m. An exception is the study by Hill et al [21], which indicated an acute decrease in vastus lateralis and gastrocnemius lateralis muscle stiffness induced by a fatiguing protocol consisting of five sets of 20 drop jumps. Furthermore, a study by Po żarowszczyk et al [26] found an acute increase in Achilles' tendon stiffness and elasticity after back squats with increasing external load (from 60 to 100% one-repetition maximum (1RM), with 10% steps). Nonetheless, the impact of particular resistance exercise intensity (load) on muscle mechanical properties is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, Klich et al [32] reported an acute increase in vastus lateralis stiffness after all-out 200 m and 4000 m track cycling, with a higher increase after 200 m. An exception is the study by Hill et al [21], which indicated an acute decrease in vastus lateralis and gastrocnemius lateralis muscle stiffness induced by a fatiguing protocol consisting of five sets of 20 drop jumps. Furthermore, a study by Po żarowszczyk et al [26] found an acute increase in Achilles' tendon stiffness and elasticity after back squats with increasing external load (from 60 to 100% one-repetition maximum (1RM), with 10% steps). Nonetheless, the impact of particular resistance exercise intensity (load) on muscle mechanical properties is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive methods, such as tensiomyography and myotonometry, assess muscles' contractile and mechanical properties, respectively. However, it seems that tensiomyography has been used more often [19,20,[22][23][24][25] than myotonometry [21,26], despite the fact that the device for myotonometry measurement (the Myoton) is more practical, being faster due to no electrical stimulation being needed, as is the case with tensiomyography (after electrode placement, the protocol consists of increasing intensity, i.e., five steps of 10 mA with a 10 s interval in between to avoid potentiation and fatigue [27]), and the device is much smaller, making it easier to transport. Moreover, the Myoton device has been validated for measurement of muscle tone and stiffness in healthy participants with "good" to "excellent" (intra-and inter-rater) reliability [28] and shows a high level of agreement compared with measurements from shear-wave ultrasound elastography [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of those solutions could include assessing viscoelastic properties, such as tendon stiffness, via myotonometry. For example, Pożarowszczyk et al (2018) reported a CA-induced increase in Achilles tendon stiffness (after single repetitions of progressive back squats at 60%–100% 1RM with 10% steps). However, the authors did not evaluate how it affects subsequent performance.…”
Section: Introductionmentioning
confidence: 99%